Rootstocks and cultivars in vineyards under double pruning - Câmara, Francisco Mickael de Medeiros (2020)
Under double pruning management, most of the wine produced is elaborated from two varieties, Syrah for red wine and Sauvignon Blanc for white wine production, mainly due to the fact that these vines were the best adapted to this technique. In this sense, two experiments were carried out in the 2018 and 2019 harvests, with the objective of evaluating varieties and rootstocks under double pruning, allowing greater diversification of winter wine labels. The first consisted in determining the effect of eight rootstocks on the agronomic and ecophysiological parameters of Merlot, Cabernet Sauvignon and Syrah vines and the second in assessing the productive and qualitative potential of some red and white varieties in two rootstocks grown during autumn-winter in southern Minas Gerais under double pruning management. The production and quality of grapes from the Cabernet Sauvignon and Merlot vines grown in the autumn-winter season can be improved using high vigor rootstocks. The adoption of IAC 766, RUPESTRIS, SO4, GRAVESAC and KOBER increased yield without affecting grape quality for all varieties. In relation to Syrah, 101-14 and 1103P showed a low grape quality and IAC 572 did not increase production. In that sense, these rootstocks can be considered less suitable. Under double pruning management, Grenache, Marselan, Mourvèdre, Tempranillo, Touriga Nacional, Petit Verdot and Syrah were the best varieties for the production of red wine and Marsanne, Muscat Petit Grain, Vermentino and Viognier for white wines, considering vigor, production and grape quality in two harvests. In general, the vigor of the IAC 766 rootstock does not compromise grape quality and can be used to increase production, mainly for Mourvèdre, Petit Verdot, Touriga Nacional and Viognier. The spur pruning technique was not adequate for Carménère under double pruning. With both experiments, it is possible to improve winter wine production through diversification, allowing winemakers to offer high quality wines to meet various types of market demands.